Sharing unwritten rules of negotiation: An effort to help leaders thrive - Julie Byerley; Kenya McNeal‐Trice; Nancy D. Spector (Journal of Hospital Medicine, 2026)
Abstract Negotiation is a skill essential for leader success yet not often trained in the academic pathway. Ideal negotiation is between at least two parties with overlapping goals where mutual benefit is achieved in a solidified agreement. For long‐term success in partnership, integrity, shared value, mutual respect, and clarity should be demonstrated during negotiation, propelling the professional relationship going forward. Negotiation is a skill often addressed in senior leadership development programs. For example, ELAM, Executive Leadership in Academic Medicine, includes negotiation skill development in its discussion‐based curriculum. For the purpose of broader distribution of skill development in negotiation, this writing attempts to share strategies for effective negotiation often referred to in such programs and discussions. Some keys to successful negotiation include cultivating a mindset of value and selectivity. Leaders must recognize when a negotiation should be occurring, specify what support is needed to succeed in the proposed endeavor, and consider how to be both strategic and realistic in their asks. For those working with search firms in employment placement, additional considerations are important. Avoiding a transactional approach and instead establishing a relationship based on shared goals, integrity, and professionalism is important. Developing a strategic mindset regarding negotiation will benefit the longevity and trajectory of one's career, and fulfillment of one's mission.